IMPACT ON MORTALITY OF THE GAP IN THE USE OF CARDIOVASCULAR PREVENTING DRUGS IN DIABETES: A POPULATION STUDY. (June 2018) - Redon, J.; Orozco, D.; Navarro, J.; Uso, R.; Trillo, J.; Fernandez, A.; Morales, F.; Sanchis, J.; Gil, V.
Abstract : Objective: Diabetes is a condition of high cardiovascular risk and drug treatment for secondary prevention of cardiovascular disease is an establish strategy recommended by guidelines. However, a wide gap exists between what the guidelines say and the real life in terms of number of class of drugs. The objective of the SATURNO study was to assess in diabetic subjects what is the impact on mortality of the gap in subjects after stroke or transitory ischemic attack (TIA), myocardial infarction (MI) or coronary revascularization (REV) based on data from Electronic Health Records (EHR). <FILE IMAGE='526_20171222055618.jpg'> Figure. No caption available. Design and method: Subjects and methods: Patients with diabetes and a diagnosis of stroke, TIA. MI or REV after January 1st, 2011 were selected from the EHR of the Valencia Community which contain all drug prescriptions. In the present study, three groups of therapy usually recommended for secondary prevention or for control of main cardiovascular risk factors were selected: aspirin, SRA blockers (ACEi or ARB) and statins. All cause mortality was obtained from official register during an observational period of 1.7+1.5 years. The survival analysis models were adjusted for group (group 0, group1, group 2, group 3), age (continuous), gender (male, female), systolic blood pressure (continuous), LDL-cholesterol (continuous), HDL-cholesterol (continuous) and diabetes treatment (yes, no). We further adjusted for hypertension treatment (yes, no) and hypertension (yes, no) (Model 2) and for dyslipidemia treatment (yes, no) and dyslipidemia (yes, no) (Model 3). R Results: : A total of 38752 patients (61% men, mean age 73 yr) were included, 22502 with stroke or TIA, MI 11692 and REV 4363. The number of subjects in each group, the number of subjects and the HRs are in the table and the survival curves in the figure Conclusions: In conclusion, the gap between guidelines and reality in the use of cardiovascular protecting drugs largely influence all cause mortality in diabetic subjects.